Two new species of Neogonyleptes Roewer, 1913 (Opiliones: Gonyleptidae: Pachylinae) from the Nahuelbuta mountain range, Chile - Pérez-Schultheiss, Jorge (Zootaxa, 2022)
Two new species of the Chilean endemic genus Neogonyleptes Roewer, 1913 are described based on specimens obtained in the Nahuelbuta mountain range, Biobío and La Araucanía Regions. The new taxa are morphologically allied to Neogonyleptes karschii (Sørensen, 1902); however, both differ from all species of the genus by their dorsal scutum area III+IV, which is armed with a large, apically bifurcate apophysis. Neogonyleptes floresi sp. nov. differs from N. pedrazai sp. nov. principally in the slender body and legs, the proximal constriction of the scutal apophysis, and the distally straight prolateral apophysis on coxa IV. Detailed descriptions, illustrations, and comparisons of the new species are given. Additionally, some comments are provided about the taxonomy of Neogonyleptes and allied genera.